Review and update of intraoperative floppy iris syndrome. (August 2011) - Sallam, Ahmed; El-Defrawy, Hany; Ross, Adam; Bashir, Samer J; Towler, Hamish MA
Intraoperative floppy iris syndrome is a well-known risk factor for complications during cataract extraction in patients who are on or who have previously used tamsulosin, the most commonly prescribed α-1 adrenergic blocker for the treatment of benign prostatic hyperplasia. It is important that both ophthalmologists and physicians appreciate the association as it occurs in a significant number of patients, and favorable visual outcome can be achieved if tamsulosin use is known before surgery and the operation is undertaken by an experienced surgeon. This article evaluates the current literature on intraoperative floppy iris syndrome and includes discussion on epidemiology, underlying mechanisms and management strategies.